Hubungan Tingkat Pengetahuan Ibu Dengan Rasionalitas Pemakaian Antibiotik Pada Balita Di Wilayah Kerja Puskesmas Dewantara Kabupaten Aceh Utara - Safira, Rahmi; Mauliza2; Syafridah, Anita (Jurnal Ilmiah Manusia Dan Kesehatan, 2023)
Antibiotics are chemical substances derived from bacteria and fungi that have the function to kill or inhibit the growth of pathogens which are generally used for the treatment of diseases caused by bacteria and the use of antibiotics must be used appropriately and according to indications. The knowledge of parents, especially mothers, about the use of antibiotics is very important in the behavior of using antibiotics in children. The purpose of this study was to determine the relationship between the mother's level of knowledge and the rationality of using antibiotics in children under five in the working area of the Dewantara Public Health Center. This type of research is an analytical study with a cross sectional design, carried out in the working area of the Dewantara Public Health Center, North Aceh Regency. Sampling with purposive sampling technique and the sample in this study were mothers who have toddlers as many as 94 people. Mothers as respondents were interviewed directly using a questionnaire. The results showed that 40.4% of respondents had good knowledge of antibiotics, 27.7% of respondents had sufficient knowledge, and 31.9% of respondents had poor knowledge. A total of 60.6% of respondents used antibiotics rationally and 39.4% of respondents used antibiotics irrationally. The conclusion is that there is a relationship between the mother's level of knowledge and the rationality of using antibiotics in children under five in the Dewantara Public Health Center, North Aceh Regency.Keywords: Antibiotic, Knowledge, Rationality